Konstytucyjna wolność przedsiębiorczości w kontekście społecznej gospodarki rynkowej – pożądane standardy regulacji - Jerzy Ciapała (Acta Iuris Stetinensis, 2023)
The subject of the study is the presentation and analysis of the freedom of entrepreneurship in the context of the social market economy. The points of reference are the provisions of the Constitution of the Republic of Poland. The author referred in particular to the jurisprudence of the Polish Constitutional Tribunal and, to a lesser extent, to the position of the doctrine. It has become justified to recall the essential features of the freedom of entrepreneurship (economic activity) in order to indicate their importance in relation to the adopted legal regulations. It must be recognized that freedom of enterprise is the first pillar of the social market economy. The other two pillars are private property and solidarity, dialogue and cooperation between social partners. In conclusion, it should be emphasized the complete lack of consistency in the adopted statutory regulations, which should comply with task standards, including the trends indicated in jurisprudence and doctrine. Therefore, we are dealing with a significant fictitious nature of constitutional regulations, which is a negative feature for the entire Polish legal order, especially since after 2016 the position of the Constitutional Tribunal is being questioned.